Perceiving the Spectrum of Pain: Wavelength-Sensitive Visual Nociceptive Behaviors in Monolayer MoS2‑Based Optical Synaptic Devices - Li, Jixiu; Zhou, Ying; Li, Yuanzheng; Yan, Chuxin; Zhao, Xin-Gang; Xin, Wei; Xie, Xiuhua; Liu, Weizhen; Xu, Haiyang; Liu, Yichun (ACS photonics, 2024)
Artificial visual nociceptors, which respond to noxious light by sending pain signals to the central nervous system, are a crucial sensory element in bionic visual systems. However, existing efforts focus on mimicking nociceptive responses to specific wavelengths of light, especially ultraviolet, with little consideration given to wavelength-sensitive nociceptive behaviors. Here, we have developed an optical synaptic device based on monolayer MoS2, featuring wavelength-sensitive visual nociceptive behaviors similar to human eyes. Except for typical synaptic functions and logical operations, essential behaviors of visual nociceptors are successfully emulated. More importantly, the device also realizes the emulation of the wavelength-sensitive nociceptor, that is, the shorter the wavelength of light the stronger the perception, and the secondary damage from long-wavelength light. Charge trapping and detrapping from interfacial defect-states, in conjunction with the band nesting effect, enable these wavelength-sensitive visual nociceptive behaviors of the devices. This work represents an important step toward endowing bionic vision systems with advanced visual capabilities.